Presence of sputum IgG against eosinophilic inflammatory proteins in asthma - Qin, Rundong; Long, Fei; Zhang, Pingan; Huang, Renbin; Hu, Hao; Guo, Yubiao; Zheng, Zhenyu; Xiao, Jing; He, Li; Peng, Tao; Li, Jing (Frontiers in Immunology, 2024)
Background Sputum immunoglobulin G (Sp-IgG) has been discovered to induce cytolytic extracellular trap cell death in eosinophils, suggesting a potential autoimmune mechanism contributing to asthma. This study aimed to explore the potential origin of Sp-IgG and identify clinically relevant subtypes of Sp-IgG that may indicate autoimmune events in asthma. Methods This study included 165 asthmatic patients and 38 healthy volunteers. We measured Sp-IgG and its five subtypes against eosinophil inflammatory proteins (Sp-IgGEPs), including eosinophil peroxidase, eosinophil major basic protein, eosinophil-derived neurotoxin, eosinophil cationic protein, and Charcot-Leyden Crystal protein in varying asthma severity. Clinical and Mendelian randomization (MR) analyses were conducted. A positive Sp-IgGEPs signature (Sp-IgGEPs+) was defined when any of the five Sp-IgGEPs values exceeded the predefined cutoff thresholds, calculated as the mean values of healthy controls plus twice the standard deviation. Results The levels of Sp-IgG and Sp-IgGEPs were significantly elevated in moderate/severe asthma than those in mild asthma/healthy groups (all p < 0.05). Sp-IgG levels were positively correlated with airway eosinophil and Sp-IgGEPs. MR analysis showed causality between eosinophil and IgG (OR = 1.02, 95%CI = 1.00-1.04, p = 0.020), and elevated IgG was a risk factor for asthma (OR = 2.05, 95%CI = 1.00-4.17, p = 0.049). Subjects with Sp-IgGEPs+ exhibited worse disease severity and served as an independent risk factor contributing to severe asthma (adjusted-OR = 5.818, adjusted-95% CI = 2.193-15.431, adjusted-p < 0.001). Receiver operating characteristic curve analysis demonstrated that the combination of Sp-IgGEPs+ with non-allergic status, an ACT score < 15, and age ≥ 45 years, effectively predicted severe asthma (AUC = 0.84, sensitivity = 86.20%, specificity = 67.80%). Conclusion This study identifies a significant association between airway eosinophilic inflammation, Sp-IgG, and asthma severity. The Sp-IgGEPs panel potentially serves as the specific biomarker reflecting airway autoimmune events in asthma.